A more perfect union - Harrison, Brigid C. (McGraw Hill, 2011)
Providing students with the tools they need to think critically about their government, A More Perfect Union offers a powerful formula for inquiry and analysis. By applying the text's three-part critical thinking framework: Then, Now, and Next (How does what happened Then and what is happening Now shape what's coming Next?), students are taught to read actively and think critically about the information they are learning